Predicting family resilience based on family communication patterns and marital commitment with the mediation of differentiation - Ehsani, Hoseinali; Shahriari Ahmadi, Mansure; Zare Bahramabadi, Mehdi; Izadi, Mahshid (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of investigating the relationship between marital commitment and family communication patterns with family resilience through the mediation of self-differentiation. Method: the current research is descriptive of the correlation type; For this purpose, a random sample of 296 people was selected from the statistical population of married men and women in Shahratkab (from West Azarbaijan province). In this research, in order to collect data from McCubbin et al.'s family resilience questionnaire (1986), Koerner and Fitzpatrick's family communication patterns questionnaire (2002), Stanley and Markman's marital commitment questionnaire (1992), Drake's self-differentiation questionnaire (2011) was used. The data obtained from the research were analyzed with SPSS-23 and AMOS-23 software. Results: The results showed that there was no relationship between self-differentiation and family resilience, so self-differentiation is not a mediator between the relationship between communication patterns and marital commitment with resilience. The Pearson correlation results showed that between the communication pattern of dialogue orientation and resilience, there is a direct and meaningful relationship at the 0.05 level, and between the communication pattern of conformity orientation, there is an indirect and significant relationship at the 0.05 level, and between marital commitment and family resilience. There was a significant and direct relationship at the 0.01 level. Conclusion: The results of structural equation modeling showed that marital commitment and family communication patterns can predict family resilience.